Burnout Stigma Inventory: Initial Development and Validation in Industry and Academia - May, Ross W.; Terman, Julia M.; Foster, Garett; Seibert, Gregory S.; Fincham, Frank D. (Frontiers in Psychology, 2020)
Although burnout is a risk factor for various negative mental and physical outcomes, its prevention is hampered by the stigma associated with burnout. The current research therefore reports on the initial development and validation of a novel measure of perceived burnout stigma. Study 1 (n = 318) describes the construction and initial evaluation of scale items derived from established mental health stigma and burnout scales. Study 2 (n = 705) then replicated the burnout stigma factor structure established in the initial study. Additionally, it evaluates relationships between occupational and school burnout stigma and indicators of mental health. Hierarchical multiple regressions showed that burnout stigma accounted for variance in depression, anxiety, and stress over and beyond that of personal burnout. Study 3 (n = 682) extended these findings via cross-lagged and bidirectional models, demonstrating that burnout stigma predicted mental health indicators six weeks later. Study 4 (n = 717) supplemented earlier exploratory and confirmatory factor analyses using item response theory to further demonstrate that perceived burnout stigma is a unidimensional construct potentially applicable to both work and school settings. Overall, the current research resulted in an eight-item burnout stigma instrument (BSI-8) with excellent psychometric properties that predicts indicators of mental health.